2014
DOI: 10.4330/wjc.v6.i10.1122
|View full text |Cite
|
Sign up to set email alerts
|

Aorto-right atrial fistula: Late complication of tricuspid valve infective endocarditis

Abstract: Abnormal connections between the ascending aorta and the cardiac chambers are rare, especially in the context of right-sided infective endocarditis (IE). Transthoracic echocardiography (TTE) with color-flow Doppler, transesophageal echocardiography (TEE), or both may be required for diagnosis. We present the case of a woman admitted with right-sided heart failure (HF) symptoms. She had a previous history of tricuspid valve IE 30 years ago. TTE and TEE revealed an aorto-right atrium fistula located just under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…It was reported that aorto-cardiac fistula occurred with infective endocarditis, blunt trauma, stab wound to the chest, ruptured aneurysms of the sinus of Valsalva, aortic dissection, congenital disorder, cardiac valve surgery, percutaneous cardiac valve implantation, heart transplantation, and autoimmune vasculitis. 1 In our cases, annular debridement was not performed, and there were no symptoms of infective endocarditis near the tricuspid valve. In addition, ARAF showed only in postoperative examination.…”
Section: Discussionmentioning
confidence: 68%
“…It was reported that aorto-cardiac fistula occurred with infective endocarditis, blunt trauma, stab wound to the chest, ruptured aneurysms of the sinus of Valsalva, aortic dissection, congenital disorder, cardiac valve surgery, percutaneous cardiac valve implantation, heart transplantation, and autoimmune vasculitis. 1 In our cases, annular debridement was not performed, and there were no symptoms of infective endocarditis near the tricuspid valve. In addition, ARAF showed only in postoperative examination.…”
Section: Discussionmentioning
confidence: 68%
“…Clinically, large aortic fistulae can present with heart failure. 24 In this patient, the aortic fistula appeared small and likely did not contribute significantly to the patient's presenting symptomatology. The chest pain in this scenario likely was due to myocardial ischemia from septic coronary emboli, also explaining the apical akinesis noted on preoperative TTE.…”
Section: Discussionmentioning
confidence: 70%
“…As the infection spreads to surrounding tissue, it inflames and weakens the myocardium, slowly eroding a path in the form of a fistula into a nearby space, such as the atrium. 3 Our literature suggests that 51.7% of AAF formations open into the right atrium. 4 Interestingly, the junctional zone between the mitral and aortic valve annulus, known as the mitral-aortic intervalvular fibrosa, is, unfortunately, ideal for abscess formation given its relative hypovascularity.…”
Section: Discussionmentioning
confidence: 96%